2020
DOI: 10.1101/2020.12.07.414607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid evolution of bacterial mutualism in the plant rhizosphere

Abstract: SummaryEven though beneficial plant-microbe interactions are commonly observed in nature, direct evidence for the evolution of bacterial mutualism in the rhizosphere remains elusive. Here we use experimental evolution to causally show that initially plant-antagonistic Pseudomonas protegens bacterium evolves into mutualists in the rhizosphere of Arabidopsis thaliana within six plant growth cycles (6 months). This evolutionary transition was accompanied with increased mutualist fitness via two mechanisms: i) imp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Several studies have reported experimental evolution as a powerful tool to explore how bacteria adapt to ecologically relevant environments. A recent study investigated the adaptive response of the PGPR Pseudomonas protegens to the A. thaliana rhizosphere in a sand system, which revealed mutations in genes encoding global regulators and genes related to motility and cell surface structure across independent populations [61] and during such adaptation, the initially plant-antagonistic P. protegens bacterium evolved into mutualists [44]. Furthermore, Lin et al (2020) observed that adaptation of Bacillus thuringiensis to A. thaliana roots under hydroponic conditions led to the evolution of multicellular aggregating phenotypes, which, surprisingly, in certain lineages were accompanied by enhanced virulence against the Galleria mellonella larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported experimental evolution as a powerful tool to explore how bacteria adapt to ecologically relevant environments. A recent study investigated the adaptive response of the PGPR Pseudomonas protegens to the A. thaliana rhizosphere in a sand system, which revealed mutations in genes encoding global regulators and genes related to motility and cell surface structure across independent populations [61] and during such adaptation, the initially plant-antagonistic P. protegens bacterium evolved into mutualists [44]. Furthermore, Lin et al (2020) observed that adaptation of Bacillus thuringiensis to A. thaliana roots under hydroponic conditions led to the evolution of multicellular aggregating phenotypes, which, surprisingly, in certain lineages were accompanied by enhanced virulence against the Galleria mellonella larvae.…”
Section: Discussionmentioning
confidence: 99%
“…For these experiments, the resulting normalized values were subjected to a One-sample t-test to test whether the mean was significantly different from 1. For pairwise competitions between the ancestor and evolved isolates on the root or in LB + xylan, the relative fitness (r) of the evolved isolate was calculated by comparing the frequency of the evolved isolate at the beginning and the end of the competition experiment as shown in equation 1 [42][43][44], in which X0 is the initial and X1 is the final frequency of the evolved isolate. The relative fitness was log2-transformed, and these values were subjected to a One-sample t-test to test whether the mean was significantly different from 0.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…Antimicrobial tolerance is also important for plant-bacteria interactions, as it can help bacteria to tolerate antimicrobials secreted by plants, such as coumarins, giving them a selective advantage in the plant rhizosphere microbiome (Stringlis et al, 2018). Such tolerance has recently been shown to evolve de novo in Pseudomonas protegens CHA0 bacterium against the antimicrobial scopoletin secreted by Arabidopsis thaliana (Li et al, 2021). Prolonged exposure to plant allelochemicals could thus select for more tolerant plant pathogen genotypes also during biofumigation and will likely be affected by the strength and duration of ITC exposure, which is important in determining whether potential tolerance or resistance mutations have enough time to sweep through pathogen populations.…”
Section: Introductionmentioning
confidence: 99%